Mechanochemical surface functionalisation of superparamagnetic microparticles with in situ formed crystalline metal-complexes: A fast novel core-shell particle formation method - Brede, F. A.; Mandel, Karl; Schneider, M.; Sextl, G.; Mueller-Buschbaum, K. (Chemical Communications, 2015)
An innovative mechanochemical method is reported for the in situ formation of crystalline metal-complexes on the surface of superparamagnetic nanocomposite microparticles. The process is demonstrated for coating Fe3O4 multicore-silica matrix particles with the 1,2,4-1H-triazole complex [ZnCl2(TzH)2]. The use of mechanochemistry demonstrates a flexible process to obtain functional shells on magnetic particle cores without the need for complicated surface-functionalisation reactions in solution. Simple mixing of the desired shell-precursors ZnCl2 and 1,2,4-1H-triazole (TzH) with the magnetic particles in a ball mill is sufficient to tailor the particle surfaces with novel functionalities while retaining the superparamagnetic behaviour.
CRIS-Team Scopus Importer:2020-04-02